GEOLOGICAL AND GEOCHEMICAL FEATURES OF THE KIZILDAĞ (AKSEKİ- ANTALYA) CHROMITE OCCURRENCES - Adnan DÖYEN; Veysel ZEDEF (Pamukkale University Journal of Engineering Sciences, 2002)
The study area is located at 20 km southwest of Seydişehir (Konya) and the chromites are cropped out in the dunitic rocks of the Kızıldağ ultramafics. The chromites are found as banded, schliren and massive occurrences and their chemical composition have a features of Alpine type chromites. These chromites can be classified as Al- rich and ferric chromites and their Cr/Fet is between 2.77 and 3.28 (mean 2.99). In the Cr/Cr+AlMg/Mg+Fe +2 binary diagram, r/Cr+Al values covers a festricted area while Mg/Mg + Fe+2 ratios distrubuted in a wider range. There is a strong negative correlation between Cr and Mg and negative (not too strong) correlation between Cr and Al.